Whatever Happened to Tory Liverpool? Success, Decline and Irrelevance since 1945 - Jeffery, David (Liverpool University Press, 2023)
In the 1968 local elections the Liverpool Conservatives won 62 percent of the vote and 78 percent of the seats on Liverpool City Council. By 1972 the party had held a majority on Liverpool's municipal government for 85 of the previous 100 years. But in 1983 they lost their last two MPs, and in 1998 they lost their final councillor. The Conservatives have not won an electoral contest in the city since. Whatever happened to Tory Liverpool? Success, decline and irrelevance since 1945 explores the history of Conservative electoral performance in Liverpool from the end of the Second World War to the present day, and challenges a number of myths regarding the city's political history: Conservative post-war success was not due to sectarian tensions or false consciousness, and neither was Conservative decline due to Margaret Thatcher. The book takes a multi-method approach to the study of Conservative Party history in Liverpool. It proposes a tripartite framework, which separates the periods of success (1945-1972), decline (1973-1986), and irrelevance (1987 onwards), and argues that each period should be explained by recourse to different phenomena. Only in this way can the complex post-war history of the Conservative Party in Liverpool truly be understood.